Preventive and Control Measures of COVID-19 Patients: A Review (Bangladesh Journal of Infectious Diseases, 2020)
Covid19 is an acute respiratory disease which is caused by a novel coronavirus. This virus has been found in January 7, 2020 from China. The virus was previously known as 2019-nCOV. This particular virus is high chance of spread. Preventive measures are very essential for the health care workers. Proper preventive measures can only be applied to stop the spread of this virus.Bangladesh Journal of Infectious Diseases, April 2020;7(suppl_1):S41-S44